Penjelasan dengan langkah-langkah:
x - 3 = 0
x = 0 + 3
x = 3
f(x) = 3x³ - 16x + a
f(3) = 3(3)³ - 16(3) + a
0 = 81 - 48 + a
0 = 33 + a
33 + a = 0
a = -33
POLINOMIAL
x – 3 = 0
f(3) = 0
3(3)³ – 16(3) + a = 0
a = 3(16) – 3(27)
a = 3(16 – 27)
a = 3 × (–11)
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Penjelasan dengan langkah-langkah:
x - 3 = 0
x = 0 + 3
x = 3
f(x) = 3x³ - 16x + a
f(3) = 3(3)³ - 16(3) + a
0 = 81 - 48 + a
0 = 33 + a
33 + a = 0
a = -33
Penjelasan dengan langkah-langkah:
POLINOMIAL
f(x) = 3x³ - 16x + a
x – 3 = 0
x = 3
f(3) = 0
3(3)³ – 16(3) + a = 0
a = 3(16) – 3(27)
a = 3(16 – 27)
a = 3 × (–11)
a = – 33 ✔